STUDI KARAKTERISASI OPTIS LAPISAN TIPIS a-SiC:H HASIL DEPOSISI METODE GLOWDISCHARGE (Makara Journal of Science, 2003)
Optical Properties of a-SiC:H Films Deposited by Glowdischarge Methods. The optical properties of amorphous silicon carbon films deposited by glowdischarge method have been studied using ultra violet-visible (uv-vis) spectroscopy. The refractive index was calculated by Swanepoel’s formula using transmission data then followed by numerical simulation. The films density tends to decrease with increasing carbon content. The widening of the optical gap by increasing carbon content indicates the enhancement of film’s transparence. Both real and imaginary parts of the dielectric constant show variation in magnitude as the carbon content increase